2015
DOI: 10.1016/j.otsr.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Knee extensor mechanism allograft reconstruction following chronic disruption

Abstract: The management of chronic extensor mechanism disruption can be complex. One of the options is allograft reconstruction. The goal of this study was to present the surgical procedure and provide preliminary results with this technique. The allograft uses the whole extensor mechanism (anterior tibial tubercle, patellar ligament, patella, quadriceps tendon). The native patella can be completely removed if the quality of the bone is poor, otherwise a bone groovecan be created to receive the allograft. The allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Patients were able to achieve pain relief, return to activities of daily living, and maintain knee range of motion at the final follow-up, although overall satisfaction rates were mild to moderate. 10 Similar functional outcomes were noted in a case series by Murgier et al, 19 although no patients in this series had a persistent extensor mechanism lag at the final follow-up. While excluded from this study, allograft extensor mechanism reconstruction in the setting of total knee arthroplasty poses additional challenges in management, with a reported 38% failure rate by Brown et al 3 …”
Section: Discussionsupporting
confidence: 84%
“…Patients were able to achieve pain relief, return to activities of daily living, and maintain knee range of motion at the final follow-up, although overall satisfaction rates were mild to moderate. 10 Similar functional outcomes were noted in a case series by Murgier et al, 19 although no patients in this series had a persistent extensor mechanism lag at the final follow-up. While excluded from this study, allograft extensor mechanism reconstruction in the setting of total knee arthroplasty poses additional challenges in management, with a reported 38% failure rate by Brown et al 3 …”
Section: Discussionsupporting
confidence: 84%
“…A large review that studied exclusively quadriceps tendon ruptures showed a fairly high incidence of poor results after open surgical repair. But when facing a complete and chronic rupture a quadriceps turndown, allograft reconstruction or synthetic graft is probably the best option [17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The gracilis tendon can also be harvested and attached to the semi-tendinosis for additional length if needed [21]. Allograft reconstruction is an alternative option that can restore active extension of the knee [22][23][24]. The main advantage of this technique is to avoid autologous harvesting, reducing the morbidity of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations